Nilai Ekonomi Ekowisata Bahari Pulau Hari Kecamatan Laonti Kabupaten Konawe Selatan Provinsi Sulawesi Tenggara - Alwi, La Ode; Ketjulan, Romy (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2010)
Development of marine tourism activity is one form of utilization of coastal resources that have no market value (non-market value). This research study about the economic value of Hari island waters as marine tourism object, tourism activities, especially diving and snorkeling tours. The results of this study cans are Used as a material consideration in the context of managing the Hari island as a tourist resort. Based on research, the existing economic value of tourism to Rp 37,772,353 per year, and the economic value of tourism carrying capacity as much as USD 268 977 384 per year.